2017
DOI: 10.1245/s10434-017-6013-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon and Radiation Oncologist Views on Omission of Adjuvant Radiotherapy for Older Women with Early-Stage Breast Cancer

Abstract: Many radiation oncologists and surgeons continue to consider omission of radiotherapy as substandard therapy and overestimate the benefits of radiotherapy. Surgeons, in addition to radiation oncologists, may have an opportunity to play a pivotal role in reducing overuse of aggressive care in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…In addition, a UK study found that women choosing to have RT omitted reported more anxiety about recurrence in clinical follow-up than women who underwent RT 27. Similarly, when surveyed, surgeons have been found to overestimate the benefit of RT and/or overestimate the patient's risk of recurrence 28. Consequently, as a medical community, we may respond differently to data that advocate for withholding established treatments rather than implementing an additional treatment.With regard to other RT treatments, our results also showed that women who did not receive chemotherapy were more likely to have HF compared to CWBI.…”
mentioning
confidence: 99%
“…In addition, a UK study found that women choosing to have RT omitted reported more anxiety about recurrence in clinical follow-up than women who underwent RT 27. Similarly, when surveyed, surgeons have been found to overestimate the benefit of RT and/or overestimate the patient's risk of recurrence 28. Consequently, as a medical community, we may respond differently to data that advocate for withholding established treatments rather than implementing an additional treatment.With regard to other RT treatments, our results also showed that women who did not receive chemotherapy were more likely to have HF compared to CWBI.…”
mentioning
confidence: 99%
“…The effects of patient overestimation of risk of disease recurrence may well relate to physician overestimation as has been demonstrated in other work. In a nationwide survey, approximately 19% of radiation oncologists and 32% of surgeons overestimated the 10‐year risk of local disease recurrence . The reluctance of many surgeons and radiation oncologists to consider the omission of RT to be a reasonable option in select older women is particularly problematic given the findings of the current study demonstrating that the most common reason given by women to omit RT was advice from a physician that RT was not needed.…”
Section: Discussionmentioning
confidence: 77%
“…The lack of consensus regarding the treatment approach in this scenario is evident in several studies of practice patterns that demonstrated only a modest decline in the use of RT after publication of the results of the CALGB 9343 trial . Our previous work evaluating clinician views concerning the omission of RT in this context found that many clinicians overestimate the benefits associated with RT and continue to consider RT omission to be substandard therapy . To the best of our knowledge, the frequency with which older patients are offered treatment without RT is uncertain, and little is known regarding their understanding of the risks and benefits of this treatment approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The omission of radiation was labeled “unreasonable” by 40% of surgeons and 20% of radiation oncologists. Many also overestimated the local‐regional recurrence rate, and 29% of surgeons and 10% of radiation oncologists believed the use of RT improved survival in this population. In a similar type survey of 999 patients, many also overestimated the risk of disease recurrence …”
mentioning
confidence: 99%